Role of MRI in Evaluation of Post-Traumatic Knee Injuries: A Prospective Study - Sanju Rawal; Rajendra KC; Subhash Chandra Yadav; Bardan Oli; Sadhan Mukhi; Krishna Thapa; Darshana Dhakal; Narayan Bohara (Journal of Universal College of Medical Sciences, 2024)
INTRODUCTION The knee joint is the largest and most complex joint in the human body. Therefore it is often affected by trauma. Magnetic Resonance Imaging (MRI) is a non-invasive imaging modality that provides detailed images of the soft tissue structures of the knee joint. The objective of this study was to evaluate MRI ﬁndings in patients with post-traumatic knee joint injuries. MATERIAL AND METHODS This prospective study was carried out using a 3.0 Tesla MRI (Magnetom Lumina) scanner in the Department of Radiodiagno- sis and Medical Imaging at Universal College of Medical Sciences & Teaching Hospital, Bhairahawa, Nepal, involving 128 patients with knee injuries, from September 2023 to February 2024. Data were analyzed using SPSS version 20. RESULTS In this study of 128 participants, 57.81% were male and 42.19% were female, with a mean age of 38.60±13.05 years. The majority of MRI ﬁndings were medial meniscus tear (51.56%), followed by anterior cruciate ligament tear (46.09%), medial collateral ligament sprain (44.53%), lateral meniscus tear (39.84%), lateral collateral ligament sprain (33.59%), and posterior cruciate ligament tear (17.97%). Our study also revealed various grades of collateral ligament injuries, including the medial and lateral ligaments. There were 59.65% of cases with a grade I medial collateral ligament sprain, followed by grade II at 33.33% and grade III at 7.02%. The grade I and grade II lateral collateral ligament sprains were 62.79% and 37.21%, respectively. CONCLUSION MRI is a non-invasive and valuable diagnostic modality that can provide an accurate diagnosis. It is often preferred over arthroscopy.